2013
DOI: 10.1002/cphc.201300313
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformation of Bovine Serum Albumin Induced by Dimethyl Sulfoxide and Probed by Fluorescence Correlation Spectroscopy and Additional Methods

Abstract: Determining the structure of a protein and its transformation under different conditions is key to understanding its activity. The structural stability and activity of proteins in aqueous-organic solvent mixtures, which is an intriguing topic of research in biochemistry, is dependent on the nature of the protein and the properties of the medium. Herein, the effect of a commonly used cosolvent, dimethyl sulfoxide (DMSO), on the structure and conformational dynamics of bovine serum albumin (BSA) protein is studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 73 publications
5
90
3
Order By: Relevance
“…18 In our experiment, we did not observe such a phenomenon because of the extremely low concentration of BSA in surfactant solutions. However, it happens only when the protein concentration is high enough.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…18 In our experiment, we did not observe such a phenomenon because of the extremely low concentration of BSA in surfactant solutions. However, it happens only when the protein concentration is high enough.…”
Section: Resultscontrasting
confidence: 53%
“…4,12,13 However, at present we still do not completely understand how the structure of a protein changes quantitatively in different charged surfactant solutions on the basis of the classical "necklace-bead" model. 18 The FCS technique was further developed for such studies. 14 Fluorescence correlation spectroscopy (FCS) captures these subtle dynamical changes at a single-protein level in terms of the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…In the near-UV region, the typical CD signals of BSA 32 were found to be almost conserved for both ASNPs and ANPs (Fig. 5B).…”
Section: Resultsmentioning
confidence: 94%
“…[26,27] It has been known for al ongt ime that low concentrations of alcohols stabilize proteins as ar esult of preferentials olvation of the alcohol molecules at the protein surface, [28] and the addition of alcohol induces a-helix formation in ac ertainc lass of proteins, [29][30][31] for which the effect is dependent on the length of the carbon chain of the alcohol. [38][39][40] In ar ecent study, [38] the effect of ethanolo nB SA was found to be bimodal;t he abundance of the secondary structural content was found to be dependent on the concentration of ethanol, which contrasts the findings of other proteins such as lysozyme [34] and melittin. At high alcohol concentrations, the We report the experimentalo bservation of nonmonotonic changes in the collective hydration of bovines erum albumin (BSA) in the presence of alcohols of varying carbon-chain lengths, that is, ethanol, 2-propanol, and tert-butyl alcohol (TBA), by using terahertz (THz) time domain spectroscopy.…”
Section: Introductionmentioning
confidence: 82%